Students’ Perceptions of Employability : A Gender Perspective - Chadha, Vikram; Sachdeva, Heena (Arthshastra Indian Journal of Economics & Research, 2019)
The purpose of this paper was to study the perception of students (on the threshold of job market) regarding the employability skills that are important to get and secure employment in the professional job market. However, the main aim of the study was to seek the difference in skills gender-wise. The questionnaire was developed to assess the perception of the skill sets considered important by students who were on the verge of getting employed. A sample of 325 students from various disciplines from nine engineering and management institutions of Punjab was considered for the study. The study found significant difference between male and female respondents’ rating for communication skills, coping to change with changing environment, decision - making skills, motivation, stress-management skills, time management skills, computer programming skills, and IT skills and on the other hand, found no significant difference between male and female respondents’ rating in case of leadership skills and problem - solving skills.